Faktor - Faktor yang Mempengaruhi Produktivitas pada Perusahaan (Studi Kasus PT Rembiga Indah) - Monika A. Rahmadona (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Low productivity remains a persistent challenge for PT Rembiga Indah, as project managers’ performance between 2022 and 2024 consistently fell short of the company’s targets despite the growing number of projects. This study aims to analyze the key determinants of productivity and provide strategic recommendations for improvement. Using a qualitative case study approach, data were collected through in-depth interviews, direct observations, and documentation, then analyzed using thematic analysis with triangulation to ensure validity. Guided by Sedarmayanti’s twelve productivity factors, the findings reveal that productivity is strongly influenced by employees’ mental attitudes, education, skills, income, social security, and opportunities for achievement. Supportive factors such as workplace environment and facilities also contribute, though less significantly. In addition, two emerging factors open communication and leadership were identified as crucial in shaping motivation, coordination, and organizational culture. These results extend Sedarmayanti’s framework by integrating contextual dimensions relevant to the construction sector. Practically, the study highlights the need for continuous training, fair reward systems, supportive leadership, and adaptive strategies to sustain productivity in the post-pandemic era.